A formal framework-based K-Maude for modelling scalable software architectures. (26th February 2019) - Sahar, Smaali; Choutri, Aïcha; Belala, Faïza
Dynamic software architecture (DySA) is one of the most important challenges and crucial problems for managing dynamically scalable software evolution. In this paper, we propose DySAL, a DySA specific modelling language, primarily based on interfaces, dealing with both evolution types: spatial reconfiguration at system level and architectural elements changes (types and behaviour) at architecture level. DySAL combines MDE and K-Maude techniques for modelling different DySA aspects (topology, behaviour, interactions, and dynamic evolution). It is defined according to an incremental and multi-level approach and may benefit from the strength of the used approaches: meta-modelling (MDE) and formal semantics (Maude). This has the advantage to manage all types of dynamic evolution and their eventual side effects. Moreover, DySAL facilitates DySA definition with multiple views while covering all phases of dynamic application development life cycle, including validation and verification. Our approach is illustrated and evaluated through a realistic example of a ubiquitous system.